E-book “A Night in Gong Mountain” - a tale on environment and space - Mohd Zahari, Muhammad Azmeer; Misman, Juritah; Nik Abdullah, Nik Narimah (Universiti Teknologi MARA, Kedah, 2023)
This e-book entitled “A Night in Gong Mountain'' aims to spread knowledge regarding cleanliness, space, and the environment. Using e-books has been demonstrated to use less paper, which benefits the environment. Additionally, reading science fiction books that emphasize the harm that littering causes to the environment may encourage readers to protect it. This e-book project would contribute towards adding literature on reducing pollution and consequently reminding people against the hazards. Moreover, the e- book is also complemented with interactive features such as pictures and audio to promote a better understanding of the book content. When the e-book was published on YouTube, audio components are also included. It is hoped that this project would reach the intended audience and promote environmental consciousness.